(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
All previous reports and practical life have proven that the human errors and devices failure are responsible for the unplanned outage of the data centers at a rate of up to 88%. And for this reason, it was important to find a way to reduce this percentage. In this study, we discuss how the Data Center Infrastructure Management system (DCIM) tool can reduce this percentage and enhance the management quality that helps to make most of the daily operations inside data centers run routinely and easily. So, the main target of this case study is finding that “if the Data Center Infrastructure Management (DCIM) tool can help to reduce the main reasons of the unplanned outage of the data centers and enhance the quality management The information technology industry consists of several stages, and one of the most important